PSYCHOLOGICAL FACTORS INFLUENCING THE PEDAGOGICAL IMAGE OF FUTURE TEACHERS IN THE EDUCATIONAL PROCESS (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the concept of the pedagogical image of future teachers, the psychological factors influencing it, and ways to develop it. The pedagogical image is closely related to the teacher’s personal qualities, communicative abilities, and social influence skills. The research results highlight the importance of psychological training, professional development programs, and the teaching of pedagogical ethics in developing a strong pedagogical image. The article also includes recommendations aimed at increasing the effectiveness of pedagogical activities.